Effects of Combined Horizontal Plyometric and Change of Direction Training on Anaerobic Parameters in Youth Soccer Players - Yiannis Michailidis; Panagiotis Venegas; Thomas Metaxas (MDPI AG, 2023)
The aim of this study is to investigate whether the combination of soccer training, plyometric training (PT), and change of direction (COD) exercises would enhance anaerobic performance to a greater extent than training on its own in youth U17 soccer players. Twenty youth players participated in this study. Players were randomly separated into two groups: the control group (CG, n = 9) and the intervention group (EX), which performed extra PT and COD exercises (EX, n = 11). The duration of the training program was six weeks. Sprint 10 m, 30 m, countermovement jump (CMJ), single leg countermovement jump (CMJ right and left), squat jump (SJ), 505 test, and Illinois agility test were measured pre and post of the training program. The performance in the 505 test improved for the EX group (right leg: p = 0.031, left leg: p = 0.004). In addition, Illinois test performance increased in the EX group (2.9%, p = 0.019). The performances of the two groups differed significantly in the Illinois agility test (p = 0.001). This study supports that a short-term combined program of PT and COD exercises can improve change of direction ability in youth U17 soccer players. The lack of effect of the intervention program on sprint and jump performance may be due to the type and volume of plyometric exercises used. The results reflect the training principle of specialization of stimulus. The improvement in performance was presented in tests that had similar characteristics to training stimuli.